Bovine Arch and Stroke Laterality. Issue 13 (7th July 2020) - Matakas, Jason D.; Gold, Menachem M.; Sterman, Jonathan; Haramati, Linda B.; Allen, Michael T.; Labovitz, Daniel; Slasky, Shira E.
Abstract : Background: Left‐hemispheric strokes are more frequent and often have a worse outcome than their right‐hemispheric counterparts. This study aimed to evaluate whether cardioembolic stroke laterality is affected by anatomical characteristics of the aortic arch. We hypothesized that laterality varies between patients with bovine versus standard arch. Methods and Results: We retrospectively identified 1598 acute cardioembolic strokes in patients with atrial fibrillation from our institutional stroke database (2009–2017). Inclusion criteria were acute anterior circulation ischemic infarct and availability of both arch and brain imaging (magnetic resonance imaging or computed tomography). Alternative causes of stroke and anomalous arch were excluded. Imaging was reviewed for stroke characterization and laterality and arch branching pattern. Bovine arch denotes a common origin of the brachiocephalic trunk and left common carotid artery. Strokes were classified as bilateral (left or right). Univariate analysis was performed using chi‐square tests. The final cohort comprised 615 patients, mean age 77 years (SD 11.8 years) with 376 women (61%) and 33% white, 30% black, and the remainder mixed/Hispanic. Standard arch (n=424) stroke distribution was left 43.6% (185), right 45.1% (191), and bilateral 11.3% (48). Bovine arch (n=191) stroke distribution was left 51.3% (98), right 35.6% (68), and bilateral 13.1% (25). Bovine arches were associated with more left‐sided strokes compared with standard arches ( P =0.018). There was an association between black race and bovine arch ( P =0.0001). Conclusions: Bovine aortic arch configuration is associated with left hemispheric laterality of cardioembolic stroke. This study enriches the understanding that arch anatomy influences stroke laterality and highlights the need for further research into the causative hemodynamic factors.